The Effect of Clavicle Support on Myoelectric Activity of Axioscapular Muscles During Computer Typing (Journal of Fiber Bioengineering and Informatics, 2018)
In the current office environment, office personnel are using computers for long periods of time ona daily basis. Consequently, there have been increased reports of work-related neck and upper limbmusculoskeletal disorders and tension neck syndrome, which affect countless office workers who usecomputers, which is also the leading cause of occupational illnesses. In rehabilitation treatment, claviclesupport that involves the use of elastic material is prescribed to exert corrective pulling forces at theupper back and stabilise the clavicle and shoulder movements. This study therefore aims to evaluatethe effect of clavicle support on the myoelectric activity of the axioscapular group of muscles, includingthe Anterior Deltoid (AD), Upper Trapezius (UT), Middle Trapezius (MT), and Lower Trapezius (LT)in young women who experience chronic neck and shoulder pain during computer use. The resultsindicate that there is an overall significant difference in the percentage of maximum voluntary electricalactivation (MVE%) of the axioscapular group of muscles between the use and absence of clavicle support(t = -2:982, p = 0:005 ‹ 0.05). Amongst the four types of muscles studied, the use of clavicle supporthas significant effects on the MT and UT muscles. The results is important to improve our understandingof clavicle support in association with muscle activity, thereby providing the basis for prescribing suitablerehabilitation treatment and intervention devices in the workplace for the reduction of musculoskeletaldisorders.
Keywords: Clavicle Support; Axioscapular Muscles; Myoelectric Activity